2007
DOI: 10.1093/ps/86.6.1100
|View full text |Cite
|
Sign up to set email alerts
|

Direct-Fed Microbial PrimaLac and Salinomycin Modulate Whole-Body and Intestinal Oxygen Consumption and Intestinal Mucosal Cytokine Production in the Broiler Chick

Abstract: The current study investigated whole-body O2 consumption, intestinal O2 consumption, and intestinal inflammation status through mucosal cytokine production on broiler chicks fed the direct-fed microbial PrimaLac. One hundred twenty 1-d-old broiler chicks were randomly assigned to 1 of 3 experimental diets: standard starter diet (control), standard starter diet with added salinomycin (SAL), and standard starter diet with added PrimaLac (DFM). Birds were housed in 2 separate rooms, the control and SAL treatments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
3
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 26 publications
4
40
3
1
Order By: Relevance
“…Ileal villus width for the prebiotic and synbiotic groups was higher than the positive control and antibiotic groups. Gunal et al (2006) and Chichlowski et al (2007) demonstrated that the villus width was not affected by probiotic and antibiotic flavomycin compared to the basal diet of broilers.…”
Section: Resultsmentioning
confidence: 99%
“…Ileal villus width for the prebiotic and synbiotic groups was higher than the positive control and antibiotic groups. Gunal et al (2006) and Chichlowski et al (2007) demonstrated that the villus width was not affected by probiotic and antibiotic flavomycin compared to the basal diet of broilers.…”
Section: Resultsmentioning
confidence: 99%
“…These enhanced digestion, absorption and efficiency of utilization of feed [2,23] . Bolton and Dewar [24] indicate that free butyric acid is absorbed very quickly in the upper digestive tract, and will likely be of limited effective.…”
Section: Discussionmentioning
confidence: 99%
“…However it has been increasing pressure to reduce or even eliminate antibiotic usage in poultry due to the development of antibiotic resistance in consumers [1] . Thus, there is an increasing interest in finding other antibiotic replacements such as prebiotics, probiotics, aromatic oils and organic acids in poultry production [2] . A probiotic was defined as a live microbial feed supplement that beneficially affects the host animal by improving its intestinal microbial balance [3] .…”
Section: Introductionmentioning
confidence: 99%
“…However, certain types of bacteria (usually called "probiotic" or beneficial bacteria) are known to enhance and contribute to the epithelial barrier (17,67). Probiotic bacteria have both direct and indirect beneficial effects on the epithelia, including enhancement of epithelial barrier function via altering intestinal microarchitecture (17), modulation of the mucosal immune system (15), and alteration of the intestinal environment (70). Probiotics inhibit pathogenic enteric bacteria via competitive exclusion, i.e., decreasing luminal pH, secretion of bacteriocidal proteins, and blocking bacterial binding to epithelium (20).…”
Section: Bacteria and Ibdmentioning
confidence: 99%